2007
DOI: 10.1158/0008-5472.can-06-4433
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein Expression Is Suppressed in Primary Human Hepatocellular Carcinomas and Is Mediated through Inactivation of CCAAT/Enhancer Binding Protein α by Phosphatidylinositol 3-Kinase Signaling Cascade

Abstract: Reactive oxygen species (ROS) resulting from chronic inflammation cause liver injury leading to transformation of regenerating hepatocytes. Metallothioneins (MT), induced at high levels by oxidative stress, are potent scavengers of ROS. Here, we report that the levels of MT-1 and MT-2A are drastically reduced in primary human hepatocellular carcinomas (HCCs) and in diethylnitrosamine-induced liver tumors in mice, which is primarily due to transcriptional repression. Expression of the transcription factor, MTF-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
96
1
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 49 publications
6
96
1
4
Order By: Relevance
“…However, we fail to find the impact of B56␤ on the phosphorylation of MTF-1, suggesting that PP2A B56␤ regulated MT expression in a MTF-1-independent manner. Consistent with these observations, a previous study reported that the activation of PI3K/AKT pathway was involved in suppression of MT expression in primary hepatocellular carcinoma (HCC) cells through inhibition of glycogen synthase kinase-3/C/EBP␣ signaling (56). PP2A B56␤ has been implicated in the dephosphorylation of AKT (57,58).…”
Section: Discussionsupporting
confidence: 61%
“…However, we fail to find the impact of B56␤ on the phosphorylation of MTF-1, suggesting that PP2A B56␤ regulated MT expression in a MTF-1-independent manner. Consistent with these observations, a previous study reported that the activation of PI3K/AKT pathway was involved in suppression of MT expression in primary hepatocellular carcinoma (HCC) cells through inhibition of glycogen synthase kinase-3/C/EBP␣ signaling (56). PP2A B56␤ has been implicated in the dephosphorylation of AKT (57,58).…”
Section: Discussionsupporting
confidence: 61%
“…These mechanisms induce cell cycle arrest at the G1/S phase and inhibit cell proliferation. However, the activation of the PI3K/Akt signaling pathway has a negative regulatory role on the expression of C/EBPα (26).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, pathway mapping showed that neurotrophin/TRK and EGF signaling were affected at lower copper concentrations. Genes that are associated with these pathways include FOS, JUN, and phosphoinositide 3-kinase regulatory subunit 3 (PIK3R3) (Supplemental Material, Additional Data File 7), factors that have been implicated in the regulation of MT transcription (3,16).…”
Section: Physiological Responses To Copper Exposurementioning
confidence: 99%